2017
DOI: 10.31235/osf.io/z76ng
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Quantitative Literature Review on Criminological Theories in Asia

Abstract: Empirical work on criminological theories in Asia has been increasing. However, few comprehensive and systematic reviews on the application of criminological theories in Asia have been conducted. Using a systematic quantitative literature review method on peerreviewed English-language journal articles, we aim to provide an overview of the use of five major criminological theories in Asia: (1)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…This balanced approach seems sensible given that decolonising knowledge is about inclusion rather than exclusion. More specifically for criminology, it has been observed that Western criminological theories can have explanatory power for understanding crime and justice issues in non-Western contexts (Suzuki et al 2017). Thus, decolonising criminology should not be misunderstood as the erasure of Western criminology.…”
Section: Syed Hussein Alatas (1928-2007)mentioning
confidence: 99%
“…This balanced approach seems sensible given that decolonising knowledge is about inclusion rather than exclusion. More specifically for criminology, it has been observed that Western criminological theories can have explanatory power for understanding crime and justice issues in non-Western contexts (Suzuki et al 2017). Thus, decolonising criminology should not be misunderstood as the erasure of Western criminology.…”
Section: Syed Hussein Alatas (1928-2007)mentioning
confidence: 99%